2009
DOI: 10.1002/pbc.22076
|View full text |Cite
|
Sign up to set email alerts
|

Clinical course and outcome in children with acute lymphoblastic leukemia and asparaginase‐associated pancreatitis

Abstract: Background-Asparaginase, an agent used in the treatment of acute lymphoblastic leukemia (ALL), is associated with the development of pancreatitis. The clinical course and long-term outcome of patients experiencing this complication has not been extensively detailed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
153
4
9

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(178 citation statements)
references
References 27 publications
(29 reference statements)
12
153
4
9
Order By: Relevance
“…Kearney et al, reported 39% of children with clinical and chemical pancreatitis did not have abnormalities detected by ultrasound; therefore, the diagnosis should not be dependent on radiographic confirmation. There was a high concordance between ultrasound and CT in detecting abnormalities, and so it may be reasonable to reserve the use of CT for those patients with persistence or worsening of clinical symptoms or laboratory findings in the setting of non-diagnostic ultrasonography [8]. While ultrasound findings were compatible with acute pancreatitis, abdominal CT (on the third day of admission) in our patient was normal.…”
Section: To the Editormentioning
confidence: 72%
“…Kearney et al, reported 39% of children with clinical and chemical pancreatitis did not have abnormalities detected by ultrasound; therefore, the diagnosis should not be dependent on radiographic confirmation. There was a high concordance between ultrasound and CT in detecting abnormalities, and so it may be reasonable to reserve the use of CT for those patients with persistence or worsening of clinical symptoms or laboratory findings in the setting of non-diagnostic ultrasonography [8]. While ultrasound findings were compatible with acute pancreatitis, abdominal CT (on the third day of admission) in our patient was normal.…”
Section: To the Editormentioning
confidence: 72%
“…This disease affects mainly children. Patients from 10 to 18 years old have an increased risk of 2.4 times to develop AAP, comparing with patients with less than 10 years old 1 . There are no studies comparing the risk among children and adults.…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…There is no relationship of dose or duration in treatment for pancreatitis, it usually appears after the fourth or sixth application. However there are reports of AAP on the first application 1,2,12,16,17 . Symptoms begin about 4 days after application, but may vary from 1 to 13 days 1,12,16 .…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%
See 2 more Smart Citations